Assessment of microplastics distribution and stratification in the shallow marine sediments of Samos island, Eastern Mediterranean sea, Greece - DE RUIJTER, VERA N.; MILOU, ANASTASIA; COSTA, VALENTINA (Mediterranean Marine Science, 2019)
Microplastics (MPs) are becoming ubiquitous in the marine environment and shallow marine sediments are one of the major sinks for MPs. In order to improve the knowledge about the environmental fate of MPs in the Aegean Sea shallow sediments, the occurrence and spatial distribution of MPs in Samos Island (Greece) was investigated for the first time, along a land-sea transect. The highest concentration of MPs was recorded at the Beach (37.2 ± 6.9 MPs/Kg DW), while the lowest concentration was recorded in the Intertidal zone (1.1 ± 0.9 MPs/Kg DW). In relation to the different shapes, Fragments and Pellets were more abundant on the Beach, while Fibers were more abundant in the Intertidal zone and barely any Sheets were found along the transect, suggesting a distribution probably governed not only by size but also morphology and perhaps chemical composition. A higher accumulation of particles was recorded in the first 10 cm of sediments, in comparison to the deepest 5 cm, indicating an increase of microplastics in the shallow marine sediments.